Performance assessment of a ventilator developed for emergency use in a resource-constrained ICU setting during the COVID-19 pandemic - Sánchez-Gambetta, S.; Arrunategui-Salas, G.; Barrios-Morocho, J.L.; Hora, R.A.; Pérez-Buitrago, S.M.; Castañeda, B.; Kwon, A.H.; Nabzdyk, C.G.S.; Casado, F.L. (BioMed Central, 2025)
The Masi mechanical ventilator was developed in Peru, designed and manufactured as a rapid-response to the healthcare emergency. Its promising pre-clinical and clinical results allowed it to be approved by the national regulatory authority to be used during the emergency. The key features of Masi are its low manufacturing cost, low dependence on a supply of high volumes of oxygen, low oxygen consumption, and flexibility between non-invasive and invasive ventilation. While Masi lacks some of the advanced features found in commercial ICU ventilators, it was specifically designed for short-term use in resource-limited and high-demand situations as an alternative when conventional devices were unavailable. This study evaluates the survival rate in intubated COVID-19 patients ventilated with Masi as compared to other conventional ventilators.
Keywords: Medicine; Intensive care medicine; Mechanical ventilation; Medical emergency; Coronavirus disease 2019 (COVID-19); Flexibility (engineering); Mechanical ventilator; Emergency medicine; Health care; Ventilation (architecture); Anesthesia; Disease; https://purl.org/pe-repo/ocde/ford#3.02.08